2024
DOI: 10.1021/acsomega.3c08486
|View full text |Cite
|
Sign up to set email alerts
|

New Cap-Holed AlP, GaP, and InP Nanotubes

Raúl Mendoza-Báez,
Dolores García-Toral,
Juan Francisco Rivas-Silva
et al.

Abstract: The structural, vibrational, and electronic properties of new inorganic X-phosphide nanotubes (ch-XPNT), with X = Al, Ga, or In and chirality of (5,5), are investigated. These new NTs display cap-hole ends, with the cap-hole features induced by the nonpassivated ends. Studies are based on density functional theory (DFT) using the M06-2X, PBE, and B3LYP functionals together with the LanL2DZ basis set. All nanostructures have been relaxed by minimizing the total energy, assuming a nonmagnetic nature and a total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 96 publications
(147 reference statements)
1
2
0
Order By: Relevance
“…Initially, the unit cell of pristine nanotubes with 10 atoms of each species resulting in Al 10 P 10 (AlPNT) and Ga 10 P 10 (GaPNT) have been generated with armchair geometry (structurally stable and formed naturally as no imaginary frequency has been observed) having chirality 2, 2, and tube lengths 8Å each and relaxed to the lowest ground state energy. After the optimization process, the diameter of the AlPNT and GaPNT is obtained 4.393 Å and 4.354 Å respectively while the energy gaps of AlPNT (2.144 eV) and GaPNT (2.017 eV) reveal their semiconducting nature, comparable with other studies on similar structures [25,27]. Further, two targeted biomarkers of breast cancer, 2-Methyloctane (C 9 H 20 ) 3,3-Dimethylpentane (C 7 H 16 ) have been optimized to the lowest ground state energy and then adsorb these optimized biomarkers into AlPNT and GaPNT nanotubes and further optimized AlPNT + C 9 H 20 , AlPNT + C 7 H 16 , GaPNT + C 9 H 20 , and GaPNT + C 9 H 20 , complexes to analyzed the feasibility of the AlPNT and GaPNT as breast cancer detection sensors.…”
Section: Computational Methodologysupporting
confidence: 85%
See 2 more Smart Citations
“…Initially, the unit cell of pristine nanotubes with 10 atoms of each species resulting in Al 10 P 10 (AlPNT) and Ga 10 P 10 (GaPNT) have been generated with armchair geometry (structurally stable and formed naturally as no imaginary frequency has been observed) having chirality 2, 2, and tube lengths 8Å each and relaxed to the lowest ground state energy. After the optimization process, the diameter of the AlPNT and GaPNT is obtained 4.393 Å and 4.354 Å respectively while the energy gaps of AlPNT (2.144 eV) and GaPNT (2.017 eV) reveal their semiconducting nature, comparable with other studies on similar structures [25,27]. Further, two targeted biomarkers of breast cancer, 2-Methyloctane (C 9 H 20 ) 3,3-Dimethylpentane (C 7 H 16 ) have been optimized to the lowest ground state energy and then adsorb these optimized biomarkers into AlPNT and GaPNT nanotubes and further optimized AlPNT + C 9 H 20 , AlPNT + C 7 H 16 , GaPNT + C 9 H 20 , and GaPNT + C 9 H 20 , complexes to analyzed the feasibility of the AlPNT and GaPNT as breast cancer detection sensors.…”
Section: Computational Methodologysupporting
confidence: 85%
“…In the same year Wan et al [23] theoretically and experimentally observed the feasibility of Ir decorated CNT to detect aniline (C 6 H 7 N) and o-toluidine (C 7 H 9 N), two biomarkers of lung cancer and concluded Ir decorated CNT is suitable for developing sensing material to diagnosis lung cancer. However, concerning the success of the implementation of nanotubes in biomedical sectors, different highly sensitive group III-IV nanotubes have been developed based on practical applications in recent years [24][25][26][27]. Phosphide-based nanotubes especially, aluminum phosphide (AlP) and gallium phosphide (GaP) nanotubes have drawn the attention of researchers due to their promising applications in different nanoelectrochemical sensors [25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation